Cell-cell death communication by signals passing through non-aqueous environments: A reply - Rhys Richard Mould; Elizabeth Louise Thomas; Geoffrey Guy; Alistair VW Nunn; Jimmy David Bell (Results in Chemistry, 2022)
The effects of the emission of low intensity light from cells and organelles, known as biophotons, or ultraweak photon emission, are not well understood and subject to debate. Potapovich & Kostyuk recently proposed that the induction of oxidative stress generates non-chemical death signals which can induce cell death in neighbouring, chemically isolated cells (termed detector cells). Given the significance of these results, here we attempt to replicate their findings. We found treatment of “inductor cells” with duroquinone dissolved in ethanol does indeed induce significant cell death in neighbouring “detector” cells relative to distant control cells (64.53 % ± 14.42 vs 99.72 % ± 6.09 cell viability), closely reproducing their original results. However, this was no longer true if the induction drug was dissolved in a less volatile solvent, suggesting that their original findings may have been a result of volatile solvent-based transmission as opposed to light-based non-chemical signalling.